2011
DOI: 10.1108/10867371111137102
|View full text |Cite
|
Sign up to set email alerts
|

Does infrequent trading make a difference on stock market efficiency?

Abstract: Purpose -After adjusting for thin trading, this study seeks to examine the market efficiency for six emerging stock markets in the Gulf Cooperation Council (GCC) countries: Bahrain, Kuwait, Oman, Qatar, Saudi Arabia and the United Arab Emirates. Design/methodology/approach -This study uses the LOMAC single variance ratio (VR) test and the Wright's rank and sign VR tests to examine informational efficiency after correcting the data for thin trading that typically characterizes these indexes. Findings -As the ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Earlier research utilized tests that accounted for the impact of limited trading activity and the Multiple Variance Ratio (MVR) test, respectively (AlKhazali, 2011;El-Temtamy & Chaudhry, 2009). During their respective research periods, these studies discovered that the SSM followed a random walk pattern and exhibited a weak-form efficiency.…”
Section: Traditional Statistical Methodsmentioning
confidence: 99%
“…Earlier research utilized tests that accounted for the impact of limited trading activity and the Multiple Variance Ratio (MVR) test, respectively (AlKhazali, 2011;El-Temtamy & Chaudhry, 2009). During their respective research periods, these studies discovered that the SSM followed a random walk pattern and exhibited a weak-form efficiency.…”
Section: Traditional Statistical Methodsmentioning
confidence: 99%
“…Liu [22] shows that the addition of liquidity factor based on zero daily trading volumes can explain established market anomalies such as size, book-to-market, and long-termcontrarian premiums. Similarly, some studies also provide the evidence that infrequent trading has a significant effect on the efficiency of stock markets [23] [24] [25] [26]. As a consequence, we construct a rearranged CRSP daily return considering the influence of infrequent trading and use a five-factor model to estimate the IV.…”
Section: Introductionmentioning
confidence: 99%
“…Studies conducted in past analyzed market efficiency using multiple tests in different contexts and found conflicting results both in favor (Al-Faryan and Dockery, 2020;Alkhazali, 2011;Al-Khazali et al, 2014;Asiri, 2008;Grieb and Reyes, 1999;Hassan, 2002;Hoque et al, 2007;Ojah and Karemera, 1999;Moustafa, 2004;Venkatesan, 2010) and against the EMH (Barnes, 1986;Darrat and Benkato, 2003;Darrat and Zhong, 2000;Fernando and Gunasekara, 2018;Omran and Farrar, 2006;Poshakwale, 2002;Squalli, 2006;Urrutia, 1995). Interestingly studies found contrasting results for same markets in different time periods, for example, Indian National Stock Exchange was efficient (Venkatesan, 2010) and inefficient (Shafi, 2014).…”
Section: Introductionmentioning
confidence: 99%